Mastering Autodesk Maya 2014 - Palamar, Todd (John Wiley & Sons, Inc., 2013)
Hands-on intermediate-to-advanced coverage of the leading 3D software Autodesk Maya is the industry-leading 3D animation and effects software used in movies, visual effects, games, and other genres. If you already know the basics of Maya and are ready to elevate your skills, then this book is for you. Nearly 1,000 pages are packed with organized, professional, and valuable insight on the leading 3D application on the market, enabling you to unlock the software's more complex features. Ideal as both a tutorial and study guide for the Autodesk Maya exam, this Autodesk Official Press.